Microbial communities in the rhizosphere of maize and cowpea respond differently to chromium contamination - Araujo, Ademir Sergio Ferreira (2023)
Chromium (Cr) contamination can affect microorganisms in the soil, but the response of the microbial community in the rhizosphere of plants grown in Cr-contaminated soils is poorly understood. Therefore, this study assessed the microbial community, by amplicon sequencing, in the rhizosphere of maize and cowpea growing in uncontaminated (∼6.0 mg kg−1 Cr) and Cr-contaminated soils (∼250 mg kg−1 Cr). Comparing Cr-contaminated and uncontaminated soils, the microbial community in the maize rhizosphere clustered separately, while the microbial community in the cowpea rhizosphere did not present clear clustering. The microbial richness ranged from ∼5000 (rhizosphere in Cr-contaminated soil) to ∼8000 OTUs (in uncontaminated soil). In the comparison of specific bacterial groups in the rhizosphere of maize, Firmicutes were enriched in Cr-contaminated soil, including Bacilli, Bacillales, and Paenibacillus. Cowpea rhizosphere showed a higher abundance of six microbial groups in Cr-contaminated soil, highlighting Rhizobiales, Pedomicrobium, and Gemmatimonadetes. The microbial community in both rhizospheres presented a similar proportion of specialists comparing uncontaminated (2.2 and 3.4% in the rhizosphere of maize and cowpea, respectively) and Cr-contaminated soils (1.8 and 3.2% in the rhizosphere of maize and cowpea, respectively). This study showed that each plant species drove differently the microbial community in the rhizosphere, with an important effect of Cr-contamination on the microbial community assembly.